Etiology, seed transmission and factors affecting development of fruit blotch of watermelon [Citrullus lanatus (Thunb.) matsum and nakai] in Northeastern Thailand - Srichumpa, Payorm; Natural, Marina P. (2000)
Thirty isolates of the fruit blotch bacterium were obtained from three locations in Northeastern Thailand. Morphological, physiological, and biochemical characterization, and pathogenicity tests identified the organism as Acidovorax avenae subsp. citrulli (Schaad et al. 1978) Willems et al. 1992 [Syn.: Pseudomonas pseudoalcaligenes subsp. citrulli (Schaad et al. 1978); P. avenae subsp. citrulli (Schaad et al. 1978) Hu et al. 1991]. No seed transmission was observed in seedlings grown from seeds gathered from naturally infected fruits and stored at room temperature or air-conditioned temperature for 1-6 months. However, seedlings from seeds of 10 different hybrids soaked in 3.5 × 109 colony-forming units (cfu) mL-1 bacterial suspension before planting, developed symptoms 7-10 days after planting, with a 1-83% disease incidence. Factors such as inoculum concentration, age of plant, wounding, and varietal resistance influenced disease development. The optimum inoculum concentration for the pathogenicity test was 3.5 × 109 cfu mL-1. Wounding predisposed fruits to infection. Differences in susceptibility to leaf infection were noted among hybrids.
Keywords: Watermelon growing; Fruit -- Development